MANAJEMEN STRATEGI ISLAMI DALAM MENGHADAPI PERSAINGAN PASAR DI HOMASTAS PAKONG PAMEKASAN - Amir (Al-Idarah, 2020)
Advances in information technology have become a trigger for business competition. Therefore, every business actor must set a reliable strategy in his business. Strategy management is a set of tools used in achieving a goal. Therefore, strategic management must be able to make all parts of a broad organization into one, integrated to achieve the final goal. Homastas shop is a type of individual business that functions to meet the household needs of the community. In the face of business competition, Homastas stores carry out several strategies including careful planning, then reliable organization, followed by identifying market tastes and identifying product marketing.